En färdig trädgård : enkätundersökning om gruppbebyggda småhusträdgårdar - Rydberg, Hanna (SLU/Dept. of Urban and Rural Development, 2009)
The main purpose with this master's thesis was to develop a survey with the intention to examine what expectations the JM AB:s customer had on a future garden and also to discuss if the lawn has a symbolic meaning in gardens.